2013
DOI: 10.2528/pierc13031908
|View full text |Cite
|
Sign up to set email alerts
|

Compact CPW-Based Zeroth-Order Resonant Antenna With Interleaving CRLH Unit Cells

Abstract: This paper proposes a compact zeroth-order resonant (ZOR) antenna with improved gain and efficiency. The proposed CRLH unit cell is based on the coplanar waveguide (CPW) structure. The proposed ZOR antenna is designed for a 2.45 GHz frequency band, and it has the characteristic of monopolar radiation. Shunt inductance is implemented by microstrip short-circuit stubs, and a metal-isolator-metal (MIM) capacitator provides series capacitance, where a large capacitance can be achieved in a small footprint. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…These compounds gained attention for their structurally unique and densely functionalized perhydrocyclobuta[ e ]indene and related frameworks . Recently, the mellolide armillaridin ( 1 ) has gained considerable attention for possessing apoptotic and radiosensitizing activity towards several cancer cell lines –,. The biosynthetically related marasmanes (including isovelleral, 4 ), exhibit broad‐spectrum antimicrobial and antifeedant activity .…”
Section: Methodsmentioning
confidence: 99%
“…These compounds gained attention for their structurally unique and densely functionalized perhydrocyclobuta[ e ]indene and related frameworks . Recently, the mellolide armillaridin ( 1 ) has gained considerable attention for possessing apoptotic and radiosensitizing activity towards several cancer cell lines –,. The biosynthetically related marasmanes (including isovelleral, 4 ), exhibit broad‐spectrum antimicrobial and antifeedant activity .…”
Section: Methodsmentioning
confidence: 99%
“…The CRLH resonator is based on transmission line (TL) structures, which is essential to realize any resonant planar antenna with no dependence on its physical dimension, and this structure supports an infinite wavelength at its fundamental mode, which is required to realize ZOR resonators [30]. A practical realization of a left-hand (LH) material includes unavoidable right-hand (RH) effects, and the CRLH resonator is able to support an infinite wavelength (β ¼ 0, with ω 6 ¼ 0) and therefore, can be used to realize any planar microwave structures [31].…”
Section: Crlh Resonatormentioning
confidence: 99%
“…Microwave structures loaded with CRLH are generally based on the insertion of inter-digital capacitors and shorted stub inductors inside the antenna or the sensor, by suitable choice of the components dimensions, and one can have desired resonant frequency [30]. It has been shown that by increasing the shunt and inductors, the antenna size can be made much smaller.…”
Section: Antennas Based On Metamaterials 41 Antenna Descriptionmentioning
confidence: 99%
“…Some research works done on sensors dealing with the chemical solution were carried out by Salim et al 44 In addition, more recent research works were performed on studying the complex permittivity or compact permittivity of the liquids, 45,46 while other research works were focusing on biological and glucose characterization 47–50 . By examining the previously published works, 1–5,16–19,23–47 it was found that the sensitivity and sensor size are still the fundamental constraints to limit microwave sensors being widely adopted. Hence, in this article, a miniaturized and improved sensitive microwave sensor with two ports is proposed to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 The resonant frequency of structure based on CRLH is characterized by the independence of its dimension. 27,28 The CRLH is based on the principle of transmission line (TL), they can be set up to obtain zeroorder resonators (ZOR), 29,30 which is the first frequency or the dominant frequency of the circuit. The CRLH has also the advantage of frequency dilation on a short band width, and this criterion is used to increase the sensitivity of the sensor, miniaturization effect is common for all the structures based CRLH.…”
Section: Introductionmentioning
confidence: 99%